Taming systematic uncertainties at the LHC with the central limit theorem - Fichet, Sylvain [UNESP] (Elsevier B.V., 2016)
We study the simplifications occurring in any likelihood function in the presence of a large number of small systematic uncertainties. We find that the marginalisation of these uncertainties can be done analytically by means of second-order error propagation, error combination, the Lyapunov central limit theorem, and under mild approximations which are typically satisfied for LHC likelihoods. The outcomes of this analysis are i) a very light treatment of systematic uncertainties ii) a convenient way of reporting the main effects of systematic uncertainties, such as the detector effects occurringin LHC measurements. (C) 2016 The Author. Published by Elsevier B.V.